The vagina bible ebook The vulva and the vagina: separating the myth from the medicine. - Gunter, Jen (2019)
Instant New York Times , USA Today , and Publishers Weekly bestseller! Boston Globe bestseller #1 Canadian Bestseller OB/GYN, The New York Times columnist, host of the show Jensplaining, and internationally bestselling author Dr. Jen Gunter now delivers the definitive book on vaginal health, answering the questions you've always had but were afraid to ask—or couldn't find the right answers to. She has been called Twitter's resident gynecologist, the Internet's OB/GYN, and one of the fiercest advocates for women's health...and she's here to give you the straight talk on the topics she knows best. Does eating sugar cause yeast infections? Does pubic hair have a function? Should you have a vulvovaginal care regimen? Will your vagina shrivel up if you go without sex? What's the truth about the HPV vaccine? So many important questions, so much convincing, confusing, contradictory mis information! In this age of click bait, pseudoscience, and celebrity-endorsed products, it's easy to be overwhelmed—whether it's websites, advice from well-meaning friends, uneducated partners, and even healthcare providers. So how do you separate facts from fiction? OB-GYN Jen Gunter, an expert on women's health—and the internet's most popular go-to doc — comes to the rescue with a book that debunks the myths and educates and empowers women. From reproductive health to the impact of antibiotics and probiotics, and the latest trends, including vaginal steaming, vaginal marijuana products, and jade eggs, Gunter takes us on a factual, fun-filled journey. Discover the truth about: • The vaginal microbiome • Genital hygiene, lubricants, and hormone myths and fallacies • How diet impacts vaginal health • Stem cells and the vagina • Cosmetic vaginal surgery • What changes to expect during pregnancy and after childbirth • What changes to expect through menopause • How medicine fails women by dismissing symptoms Plus: • Thongs vs. lace: the best underwear for vaginal health • How to select a tampon • The full glory of the clitoris and the myth of the G Spot . . . And so much more. Whether you're a twenty-six-year-old worried that her labia are "uncool" or a sixty-six-year-old dealing with painful sex, this comprehensive guide is sure to become a lifelong trusted resource.